FAKTOR PENENTU PENGUNGKAPAN TANGGUNG JAWAB SOSIAL DAN DAMPAKNYA TERHADAP NILAI PERUSAHAAN (Studi pada perusahaan pertambangan di Bursa Efek Indonesia 2013 - 2016) - SISCA SANTIKA ; Dr. Roekhudin, M.Si., Ak., CSRS., CA,Dr. Erwin Saraswati , Ak., CPMA., CSRA
This research aims to test the determining factor of corporate social responsibility _x000D_ disclosure and it’s effect on firm value and the data of the research are 16 mining_x000D_ companies registered in the Indonesia Stock Exchange during the years of_x000D_ observation in 2013-2016. In addation, the analysis technique used in this study_x000D_ are multiple regression analysis and simple regression analysis by using a_x000D_ software named SPSS version 16. The results of this research show that the firm_x000D_ size and public ownership are able to increase disclosures of corporate social_x000D_ responsibility, while profitability, leverage and liquidity are unable to increase_x000D_ the disclosure of corporate social responsibility since the disclosure of corporate_x000D_ social responsibility is an obligation that must be done by the company regardless_x000D_ of the level profitability, leverage and liquidity. Meanwhile, the growth is unable_x000D_ to increase the disclosure of corporate social responsibility, since companies with_x000D_ a high growth rate would prefer to use the costs for production activities. The_x000D_ Board of Independent Commissioners proved to be unable to increase corporate_x000D_ social responsibility disclosure because the commissioners is not capable to play_x000D_ an important role in the determination of the strategy. Futhermore, the disclosure_x000D_ of corporate social responsibility is unable to increase the value of the company_x000D_ because the investors in Indonesia tend to purchase and sell shares without_x000D_ considering the survival of the company in the long-term. _x000D_ _x000D_ Key words: determinants, corporate social responsibility disclosure, firm value.